Different doses of methamphetamine alter long-term potentiation, level of BDNF and neuronal apoptosis in the hippocampus of reinstated rats - Shahidi, Siamak; Komaki, Alireza; Sadeghian, Reihaneh; Asl, Sara Soleimani (The journal of physiological sciences, 2019)
Methamphetamine (METH) is a psychostimulant. The precise mechanisms of its effects remain unknown and current relapse treatments have low efficacy. However, brain-derived neurotrophic factor (BDNF) and neuronal plasticity are essential contributors, despite paradoxical reports and a lack of comprehensive studies. Therefore, we investigated the effects of different doses of METH on long-term potentiation (LTP), BDNF expression and neuronal apoptosis in the hippocampus of reinstated rats. Rats were injected intraperitoneally with METH (1, 5, or 10 mg/kg) or saline, and trained in a conditioned place preference paradigm. Following implementation of the reinstatement model, electrophysiology, western blotting and TUNEL assay were performed to assess behavior, LTP components, BDNF expression, and neuronal apoptosis, respectively. The results demonstrated that the preference scores, population spike amplitude and BDNF expression markedly decreased in the METH (10 mg/kg) group compared with the other groups. In contrast, METH (5 mg/kg) significantly increased these factors more than the control group. There was no change in variables between METH (1 mg/kg) and the control group. Also, apoptosis of the hippocampus was increased in the METH (10 mg/kg) group compared with the METH (5 mg/kg) group. These results suggest that alterations in synaptic plasticity, expression of BDNF and neuronal apoptosis in the hippocampus has a vital role in the context-induced reinstatement of METH seeking.